Pengaruh Model Pembelajaran AIR (Auditory, Intellectually, Repetition) Terhadap Motivasi Belajar Siswa - Hikma, Widya Ainur; Hasmiati, Hasmiati; Qadrianti, Laeli (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study aims to test whether the use of the AIR (Auditory, Intellectually, Repetition) learning model has an effect on students' learning motivation in Islamic Religious Education subjects at SMK Negeri 1 Sinjai. The population of this study was all grade X students at SMK Negeri 1 Sinjai, totaling 143 students. The sample determination used the Slovin formula and obtained 105 students as samples. The data collection techniques used were questionnaires and documentation. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that learning activities using the Auditory, Intellectually and Repetition learning model have an effect on students' learning motivation in Islamic Religious Education subjects at SMK Negeri 1 Sinjai, as evidenced by the hypothesis test which shows that the P Value (Sig a) is 0.000 <0.05, which means that learning activities using the Auditory, Intellectually and Repetition learning model have an effect on students' learning motivation in Islamic Religious Education subjects at SMK Negeri 1 Sinjai. The R square value (Coefficient of Determination) is 0.209 or if presented as 20.9%, it can be said that the water learning model has an effect on students' learning motivation.